Validity of the Falls Risk for Older People in the Community (FROP-Com) tool to predict falls and fall injuries for older people presenting to the emergency department after falling - Mascarenhas, M.; Hill, Keith; Barker, A.; Burton, Elissa (Springer Verlag, 2019)
© 2019, Springer Nature B.V. The aims of this study were to (1) externally validate the accuracy of the Falls Risk for Older People in the Community (FROP-Com) falls risk assessment tool in predicting falls and (2) undertake initial validation of the accuracy of the FROP-Com to predict injurious falls (requiring medical attention) in people aged = 60 years presenting to emergency departments (EDs) after falling. Two hundred and thirteen participants (mean age = 72.4 years; 59.2% women) were recruited (control group of a randomised controlled trial). A FROP-Com assessment was completed at a home visit within 2 weeks of ED discharge. Data on falls and injurious falls requiring medical attention were collected via monthly falls calendars for the next 12 months. Predictive accuracy was evaluated using sensitivity and specificity of a high-risk FROP-Com classification (score = 19) in predicting a fall and injurious falls requiring medical attention. Fifty per cent of participants fell, with 60.4% of falls requiring medical attention. Thirty-two per cent were classified as high, 49% as moderate and 19% low falls risk. Low sensitivity was achieved for the FROP-Com high-risk classification for predicting falls (43.4%) and injurious falls (34.4%), although specificity was high (79.4% and 78.6%, respectively). Despite the FROP-Com’s low predictive accuracy, the high fall rate and high falls risk of the sample suggest that older people who fall, present to ED and are discharged home are at high risk of future falls. In high-falls-risk populations such as in this study, the FROP-Com is not a valid tool for classifying risk of falls or injurious falls. Its potential value may instead be in identifying risk factors for falling to direct tailoring of falls prevention interventions to reduce future falls.